Causality between regional stock markets: A frequency domain approach - Gradojević Nikola; Dobardžić Eldin (Panoeconomicus, 2013)
Using a data set from five regional stock exchanges (Serbia, Croatia, Slovenia, Hungary and Germany), this paper presents a frequency domain analysis of a causal relationship between the returns on the CROBEX, SBITOP, CETOP and DAX indices, and the return on the major Serbian stock exchange index, BELEX 15. We find evidence of a somewhat dominant effect of the CROBEX and CETOP stock indices on the BELEX 15 stock index across a range of frequencies. The results also indicate that the BELEX 15 index and the SBITOP index interact in a bi-directional causal fashion. Finally, the DAX index movements consistently drive the BELEX 15 index returns for cycle lengths between 3 and 11 days without any feedback effect.